Suicide Risk, Self-esteem and Family Support among Community School Going Adolescents of Kathmandu Valley, Nepal: A Cross-sectional Study (Journal of BP Koirala Institute of Health Sciences, 2022)
Background: Suicide is one of the major public health concerns today in all age groups. Suicide has often been neglected in adolescents. We aimed to find out the prevalence of suicidal ideas and attempts, and explore its association with family support and self-esteem among school going students of Kathmandu valley.Methods: We performed a cross-sectional study using a semi structured proforma, P4 Suicide screener, Nepali family support and difficulties scale and Rosenberg self-esteem scale among 211 students of grade eight to ten of two community schools of Kathmandu valley. Socio-demographic and clinical data were tabulated and descriptive analysis were done. The tests for normal distribution were performed initially and then Fisher exact test (categorical) and Mann Whitney U test (continuous variable) were used as applicable.Results: The P4 suicide screen showed 27.96% of the students to be positive. The risk stratification revealed that the maximum percentage (76.3%) of screen positive students had higher risk. The group of students who had no suicidal risk had significantly higher score in family support and difficulty scale as compared to the student with suicidal risk. However, the self-esteem score had no statistically significant difference between the two groups.Conclusion: The suicide risk was present among one-third of the students with high risk among the majority. Considering this high prevalence, it is crucial for parents, teachers and all healthcare providers to be proactive and look for warning signs with all children and adolescents.